High-Performance Thin-Film VCSELs Integrated with a Copper-Plated Heatsink - Moon, Sunghyun; Yun, Yeojun; Kwon, Ohdo; Nam, Yonghyun; Kim, Donghwan; Choi, Won jin; Kim, Sangin; Lee, Jaejin (Advanced Materials Interfaces, 2023)
High-performance continuous-wave (CW) vertical-cavity surface-emitting lasers (VCSELs) rely on efficient thermal management for which top-emitting 930 nm thin-film VCSELs are integrated with a copper-plated heatsink by using a double-transfer technique, exhibiting the low-power consumption, high-power, and temperature-stable VCSEL operation. In this study, the top-emitting 930 nm thin-film VCSEL structures, including the highly n-doped GaAs ohmic and lattice-matched InGaP etch-stop layers, are epitaxially grown via a low-pressure metalorganic chemical vapor deposition (LP-MOCVD) system. The electrical and optical properties of the substrate-removal thin-film VCSELs are investigated under CW operation, compared to those of the bulk-type VCSELs onto the n-GaAs substrates. The differential series resistance (85.92 Ω) of the thin-film VCSEL is 9.16% lower than 94.59 Ω of the bulk-type VCSEL onto the n-GaAs substrates. The thermal resistance (607 K W−1) of the thin-film VCSEL is 46.33% lower than 1131 K W−1 of the bulk-type VCSEL, by which the maximum peak power (11.70 mW) of the thin-film VCSEL at 24 mA is 12.07% higher than 10.44 mW of the bulk-type VCSEL at 22.40 mA under room temperature (25 °C).
Keywords: Heatsink; High power; High reliability; Low-power consumption; Lower-power consumption; Performance; Thin-film vertical-cavity surface-emitting laser; Thin-films; Top-emitting; Vertical-cavity surface emitting laser; heatsink; high power; high reliability; low-power consumption; thin-film VCSEL